Similarity and polarization in groups - Mariagiovanna Baccara; Leeat Yariv (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2010)
The focus of this paper is the endogenous formation of peer groups. We study a model in which agents choose their peers prior to making decisions on multiple issues. Agents differ in how much they value the decision outcomes on one issue relative to another. While each individual can collect information on at most one issue, all information is shared within the group. Thus, the group's preference composition affects the type of information that gets collected. We characterize stable groups, groups that are optimal for all their members. When information costs are low, stable groups must be sufficiently homogeneous. Furthermore, stability requires more similarity among extremists than among moderate individuals. When information costs are substantial, a free rider problem arises, and makes extreme peers more desirable, as they are more willing to invest in information acquisition. We show that, as information costs grow, polarization appears and becomes increasingly pronounced in stable groups.
Keywords: D82; D85; 330; Homophily; Polarization; Group Formation; Information Collection